Determinants of low birth weight and effect of indoor air pollution on birth weight: A case–control study in a tertiary care centre of Hubballi, Karnataka - Kashavva B. Andanigoudar; Mahesh Kurgodiyavar; N Roopakala; Dattatraya D. Bant (Journal of Family Medicine and Primary Care, 2025)
Background: The majority of all low birth weight (LBW) babies are born in developing countries, and half of the population in developing nations use solid fuels as their primary source of energy for cooking. An association between household use of solid biomass fuels and reduced newborn weight has been found in several countries. India has a high prevalence of LBW babies, and 88% of the population use solid fuels for cooking. Objectives: To evaluate the determinants of low birth weight and to assess the effect of exposure of pregnant women to indoor air pollution on the birth weight of newborns. Methodology: A case–control study was conducted on singleton newborn babies of KIMS hospital, Hubballi. A structured pretested validated questionnaire was administered to 146 participants including 73 cases (new born babies with birth weight <2.5 kg) and 73 controls (new born babies with birth weight ≥2.5k g). The questionnaire comprised of sociodemographic characteristics, obstetric history, medical illnesses, and the current pregnancy with its outcomes and indoor air pollution. Results: The study found a significant association between low birth weight and a history of low birth weight, no intake of albendazole tablets, hemoglobin levels during pregnancy, exposure to smoke from mosquito repellent coils during pregnancy, burning of volatile liquids at home, and duration of exposure to indoor air pollutants during pregnancy. Conclusion: Indoor air pollution significantly affects the baby’s birth weight. Appropriate antenatal care and health education to overcome indoor air pollution can significantly improve the birth weight of the baby.